Reviewing the Theories of Nationalism: Historicizing, Classifying and Inquiring the Conceptualization - Ömer Senan Arslaner (Lectio Socialis)

(untitled)
As neoliberalism ended class-based politics, which was a strategic priority for capital, the relations with the economic system no longer determined the political preferences. Instead, identities have become one of the main axes of political competition in identity politics. Relatedly, nationalism has come to the fore, especially after the 1990s. One of the factors affecting this was globalization, which puts nation-state sovereignty on the target board to remove all obstacles in front of financial capital. As a reaction, initiatives to strengthen state sovereignty have searched the ground for implementation, reminding the economic nationalism discourse of the 1960s and 1970s. Secondly, while the newly independent nation-states that emerged with the collapse of the Soviet Union and Yugoslavia consolidated their authority, the ethnic conflicts they encountered inflamed nationalism. Third, the rise of international migration has "otherized" some groups, especially Muslims, for Western political orders -contrary to the appeal of cultural pluralism- and increased nationalist reflexes. In this context, it has become vital to examine how the concept of nationalism has been approached theoretically. In this review article, the debate on nationalism dwelled on the framework of the developments that led to the emergence of nations and nationalisms. This framework also included the definitions of nation and nationalism.